State Management of Kibersafety in Hybrid War Conditions - Yakymchuk , Oleg (Theory and Practice of Public Administration, 2019)
The system of public administration in Ukraine has undergone significant transformations in recent years due to the European integration course of the state on the one hand, and from the other – the increasing negative impacts of the aggressor State, Russia in the hybrid war, including Information. The insufficient level of development of society informatization in Ukraine, as indicated by experienced international experts, negatively affects the indicators security of the State, socio-psychological state of citizens, economic development of the State, Financial stability of the national currency, political situation, etc. Today, the global trend is to increase globalization processes, growth of services and intangible production, the impact of information and communication Technologies (ICT) on the processes of development of scientific and technological progress, including large-scale , deep and dynamic penetration of information technologies (IT) into all spheres of life of society, business entities and state. Socially unprotected groups, low-income citizens, the person of the older generation, residents of small settlements are increasingly removed from the benefits provided by a single information space. In addition, a serious problem is the lack of skills to use the growing arsenal of network services, including the inability to expand the range of opportunities provided by the citizen. That is why the first place is now necessary to appeal to the positive international experience in the field of information development of society, the study of mechanisms and Instruments of state information policy regulation for effective implementation in Ukraine taking into account modern political, economic, social, mental factors and peculiarities of Ukrainian society.